2017
DOI: 10.1007/s00403-017-1748-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum fatty acid profile in psoriasis and its comorbidity

Abstract: Psoriasis is a chronic inflammatory skin disease that is accompanied by metabolic disturbances and cardio-metabolic disorders. Fatty acids (FAs) might be a link between psoriasis and its comorbidity. The aim of the study was to evaluate serum concentrations of FAs and to investigate their association with the disease activity, markers of inflammation and possible involvement in psoriatic comorbidity: obesity, type 2 diabetes and hypertension. We measured 14 total serum fatty acids content and composition by ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 36 publications
2
40
0
13
Order By: Relevance
“…Even though the total FA concentration was similar to that in the control group, there were significant differences in individual acids. A significant rise in the n-6/n-3 ratio and a reduction in omega-3 PUFAs were observed [42]. A positive correlation was identified between PASI and the ratio of n-6/n-3 PUFAs, and a negative correlation was found between PASI and eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), and n-3 PUFAs.…”
Section: Fatty Acidsmentioning
confidence: 95%
See 4 more Smart Citations
“…Even though the total FA concentration was similar to that in the control group, there were significant differences in individual acids. A significant rise in the n-6/n-3 ratio and a reduction in omega-3 PUFAs were observed [42]. A positive correlation was identified between PASI and the ratio of n-6/n-3 PUFAs, and a negative correlation was found between PASI and eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), and n-3 PUFAs.…”
Section: Fatty Acidsmentioning
confidence: 95%
“…A number of studies have shown a decrease in the total concentration of phospholipids, phosphatidylethanolamine, lecithin, linolenic acid, and docosatetraenoic and docosapentaenoic acids [9,41]. Some studies demonstrate an increase in some fractions, such as palmitic acid and palmitooleic acid, while others show no differences [9,27,42]. An increase in CER, both in skin lesions and in the serum of patients with psoriasis, has been shown, however only in association with the severe course of the disease.…”
Section: Lipidy W Surowicy Cholesterole Trójglicerydy I Apolipoproteinymentioning
confidence: 99%
See 3 more Smart Citations